Clinical significance of half‐lives of tumor markers α‐fetoprotein and des‐γ‐carboxy prothrombin after hepatectomy for hepatocellular carcinoma. Issue 3 (8th September 2017) - Tsukamoto, Masayo; Nitta, Hidetoshi; Imai, Katsunori; Higashi, Takaaki; Nakagawa, Shigeki; Okabe, Hirohisa; Arima, Kota; Kaida, Takayoshi; Taki, Katsunobu; Hashimoto, Daisuke; Chikamoto, Akira; Ishiko, Takatoshi; et al.
Abstract : Aim: The prognostic significance of the half‐lives (HLs) of α‐fetoprotein (AFP) and des‐γ‐carboxy prothrombin (DCP) in patients undergoing hepatectomy for hepatocellular carcinoma (HCC) is unclear. We evaluated the HLs of AFP and DCP in a cohort of such patients. Methods: This study included data on 202 patients with HCC who underwent curative hepatectomy and had preoperative AFP concentrations ≥100 ng/mL or DCP ≥200 mAU/mL. We calculated the HLs of AFP and DCP from their values just before and 1 month after hepatectomy. We identified three groups: a normalization group, tumor marker concentrations within normal range 1 month post‐hepatectomy; a long group, HL of AFP ≥7 days or DCP ≥4 days; and a short group, remaining patients. We evaluated associations between HL and prognosis. Results: Three‐year recurrence‐free survival (RFS) in the normalization ( n  = 70), short ( n  = 71), and long groups ( n  = 61) was 41.3%, 46.0%, and 16.8%, respectively ( P  = 0.002). Five‐year overall survival (OS) of normalization, short, and long groups was 72.6, 70.6 and 43.8%, respectively ( P  = 0.002). Multivariate analysis revealed that long HL is an independent risk factor for poor RFS (hazard ratio [HR] 2.21, P  = 0.0006) and poor OS (HR 2.70, P  = 0.004). The extrahepatic recurrence rate was 21.3% (13/61) in the long group, which is higher than in the normalization group (8.6%, 6/70) ( P  = 0.04) and short group (9.9%, 7/71) ( P  = 0.07). Conclusion: Post‐hepatectomy HLs of AFP and DCP are predictors of long‐term outcome in patients with HCC.